Pourquoi filmer sa culture ? Rituel et patrimonialisation en Amazonie brésilienne - Chloé Nahum-Claudel; Nathalie Pétesch; Cédric Yvinec (Journal de la Société des Américanistes)
This article examines three detailed case studies (Karajá, Enawenê-nawê, Suruí of Rondônia) in which films of collective and spectacular ritual are produced as a means to display Amazonian indigenous “culture”. The article examines the reasons for the choice of particular rituals as the incarnation of culture; the political and symbolic implications of the performance of culture; the modalities through which films are produced; the choice of spectators for this culture-on-film and the play of revelation and concealment of ritual knowledge which the filmic media enables. The creation of cultural patrimony, which occurs within the framework of relations with Brazilian and international society, fits into a key dynamic of Amazonian social reproduction and inter-ethnic relations, that is, the drive to integrate alterity.